Female multidimensional poverty in Brazil in 2015 - Batista, Ravena de Carvalho Reis (2021)
Studies developed by the Social Sciences have been dedicated to the analysis of the feminization of poverty, exploring conditions of the different sources of deprivation to which women are subjected. Thestudy aims to analyze female multidimensional poverty in Brazil in 2015, calculating the level of multidimensional poverty, using the Alkire-Foster method. The results showed that 13.63% of Brazilian women were considered multi-dimensionally poor, and that the greatest deprivations suffered by them are in access to formal education and good conditions for domestic work.